Creative thinking in Islam: concepts and issues - Badi, Jamal Ahmed Bashier (InThought, 2021)
The understanding and definition of creativity is based on the background of the various Western writers. However, this study aims to show the common understanding and existing differences among the literature and to make further references to other civilizations for a comprehensive understanding and application of creative thinking. Therefore, the remaining part of this study is organized as follows: (2) Definition of creativity from Western literature, (3) Differing Views on the definition and understanding of Creativity, (4) the Challenges in the understanding and application of creativity (5) Ethics of Creativity (6) Dark side of Creativity (7) Advances in Creativity Research (8) Conclusion.